Olhar fonoaudiológico sobre as anomalias da diferenciação sexual: um estudo exploratório - Galli, Daniela Martins (2009)
This issue encompasses a bibliography exploratory study on the Disorders of Sexual Development (DSD). Its goal is to describe, analyze and systematize information on such disorders, especially in terms of ways of conceiving them and treating them to subsidize and give the speech support approach with this profile, through multi-and interdisciplinary teams. DSD questions, throughout life, organizational issues, sexuality and psychological constitution, including developments affecting the speech work for language sequels and damages often occur (oral and/or writing), in the voice and hearing. This issue was motivated by concerns and questions arising from clinical practice with patients with DSD. In the light of the lack of speech therapy studies on the subject, it was decided to make from clinical inquiries the axis of an initial systematization of the original (specialized) literature, introducing their questions to speech therapists, as well as highlighting the relevance of their work in this field. The literature points out the severe organic problems of DSD (genetic, hormonal, etc.), regarding distress and suffering of parents and patients due to the controversial, complex and multifaceted condition that overcome problems related to human sexuality. Ultimately, the problem surrounding these anomalies sets itself as a generating field of disorders of various sources: affective-related, organizational, communication, among others; which demands from health professionals specific training, standpoint, clinical listening and teamwork